2021
DOI: 10.3390/atmos12030369
|View full text |Cite
|
Sign up to set email alerts
|

Drought in South Asia: A Review of Drought Assessment and Prediction in South Asian Countries

Abstract: South Asian countries have been experiencing frequent drought incidents recently, and due to this reason, many scientific studies have been carried out to explore drought in South Asia. In this context, we review scientific studies related to drought in South Asia. The study initially identifies the importance of drought-related studies and discusses drought types for South Asian regions. The representative examples of drought events, severity, frequency, and duration in South Asian countries are identified. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…There is a paucity of studies concerning drought projections in the southern slope of Central Himalaya, Nepal. Further, Chandrasekara et al (2021) also suggested a drought projection study over south Asian countries. Concerning the lack of the projected drought conditions over Nepal, a reliable study to quantify future drought conditions is undoubtedly needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of studies concerning drought projections in the southern slope of Central Himalaya, Nepal. Further, Chandrasekara et al (2021) also suggested a drought projection study over south Asian countries. Concerning the lack of the projected drought conditions over Nepal, a reliable study to quantify future drought conditions is undoubtedly needed.…”
Section: Introductionmentioning
confidence: 99%
“…Nepal is located in the south Asian monsoon region; however, it has a long history of frequent seasonal and annual drought (Hamal et al 2020b(Hamal et al , 2021Sharma et al 2021). The historical drought events were recorded in 1972in , 1977in , 1982in , 1992in , 1994in , 2002in , 2004in , 2005in , 2006in , 2008in -2009in (Chandrasekara et al 2021Dahal et al 2016;Sharma et al 2021;Wang et al 2013). Moreover, most previous drought studies have used Standard Precipitation Index (SPI) for drought quantification, which uses only precipitation as a fundamental variable (McKee et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…South Asian countries have recently been experiencing frequent drought incidents, and the Standardized Precipitation Index (SPI) has mostly been adopted in South Asian countries to quantify and monitor droughts [33]. Khatiwada and Pandey [34] identified that the SPI is focused foremost on capturing the duration and intensity of drought in the Karnali river basin, Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…(Yamamoto & Nakada, 2015) Storm Subsidence, low-lying areas, shallow bays, tropical cyclone (Firman et al, 2011;Gettelman et al, 2018) Wind speed, storm intensity, increased rainfall from tropical cyclones, humidity, large scale atmospheric circulation (Gettelman et al, 2018;Guzman & Jiang, 2021;Kossin et al, 2014Kossin et al, , 2020Wernli et al, 2002) Population density, hazardous materials, dense infrastructure (Firman et al, 2011;Young et al, 2004) Building design and construction, socio-economic inequality, awareness and preparedness (Firman et al, 2011) e.g., Cyclones have seldom hit southern Vietnam, but a tropical storm and 1m storm surge is possible; the lack of awareness in this region could lead to disastrous damage, and significant loss of lives. (Thao et al, 2014) Drought -Precipitation, evapotranspiration, historic evolution of soil moisture, temperature (Palmer, 1965;Seneviratne et al, 2010;Vicente-Serrano et al, 2010) Population density, agriculture; livestock (Chandrasekara et al, 2021;Singh et al, 2014) Water governance, socio-economic inequality, livelihood (Barlow et al, 2002;Pulhin et al, 2010;Zhang & Zhou, 2015) e.g., The Lower Mekong River Basin (Thailand, Cambodia, Laos, and Vietnam) is vulnerable to increasing drought according to future projections . Droughts in this region affect the socio-economic conditions of over 60 million people and result in economic losses in the hundreds of millions USD.…”
Section: Underestimating Hazardmentioning
confidence: 99%